REQUESTIVE UTTERANCES IN SPOKEN JAVANESE OF TEGAL - Mualimin, Mualimin; Marsono, Marsono; Suhandano, Suhandano (Faculty of Humanities, Diponegoro University, 2019)
StudyingÂ language use as a part of the culture has been carried out for many years in many parts of the world, including in Indonesia. Indonesia which has various cultures has hundreds of local languages in which one of them is Javanese spoken in Tegal. This study is aimed at exploring how the Javanese dialect spoken in Tegal is used in drama radio programs on Pertiwi Radio of Slawi, the capital city of Tegal Regency.The data of the research are in the forms of uttrerances spoken by the characters of the drama containing requestive speech acts using a sociopragmatic approach. The findings of the research show that requestive utterances found in the drama are expressed both directly and indirectly. The direct requestive speech acts are mostly conveyed in utterances with imperative mood, Â while indirect requestive ones are in the forms of declarative and interrogative utterances. The choice of utterances is influenced by context of social factors where the language is used and is related to request strategy.